Inflation Dynamics in Mongolia : Understanding the Roller Coaster - Bersch, Julia; Barnett, Steven; Ojima, Yasuhisa (Washington, D.C. : International Monetary Fund, 2012)
Inflation in Mongolia resembles a roller coaster ride with sharp rises and steep drops. Understanding why is critical for formulating and assessing monetary policy. Food prices are found to be a key driver of inflation, and, not surprising given Mongolia's geography, are determined primarily by local supply conditions, highly seasonal, and subject to large but short-lived shocks (usually weather related). Nonetheless, demand factors are also found to be significant in explaining price movements and empirical evidence suggests that a 10 percent increase in government wages, for example, would push up underlying inflation by 1 percentage point. So, while inflation will remain volatile due to agricultural shocks, there is space for macroeconomic stabilization policy to help reduce inflation volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet